Water quality and phytoplankton assessment in three selected waterfalls of Kuching and Serian districts, Sarawak - Jasmina, Majit (Universiti Malaysia Sarawak (UNIMAS), 2008)
Two tridentate Schiff base ligands, containing a donor set of ONN and ONS were prepared by the reaction of salicylaldehyde with 2-aminothiophenol and benzhydrazide with 2- benzoylpyridine. Four organotin(IV) complexes (3-6) of salicylaldehyde-2-aminothiophenol ligand (1) with RnSnCl4-n (n = 1, 2, 3) have been synthesized in the presence of base in absolute chloroform in 1:1 mole ratio under nitrogen atmosphere. Another three organotin(IV) complexes (7-9) of 2-benzoylpyridinebenzhydrazone ligand (2) with RnSnCl4-n (n = 1, 2, 3) have also been synthesized in the presence of base in absolute methanol in 1:1 mole ratio. Schiff base ligands (1-2) and their organotin(IV) complexes (3-9) have been characterized by CHN analyses, UV-visible, molar conductance and FTIR spectral analyses. Among them, ligand (2) and complex (7) have also been determined by 1H NMR spectral studies. All organotin(IV) complexes (3-9) are non-electrolytic in nature. Based on the FTIR and 1H NMR analyses, ligand (1) acts as dinegative tridentate ligand in the organotin(IV) complexes (3-6). Whereas the ligand (2) acts as uninegative tridentate nature in its organotin(IV) complexes (6- 9). A five-coordinated molecular structure has been proposed for the organotin(IV) complexes (3-6) of ligand (1) while a six-coordinated molecular structure has been proposed for organotin(IV) complexes (7-9) of ligand (2).